Accuracy of ESI triage, qSOFA Score And Their Combinations As Predictor of Sepsis Prognosis - Nikma Alfi Rosida; Teguh Wahdju Sardjono; Laily Yuliatun (Universitas Aisyah Pringsewu, 2022)
This study is to identify the combination of ESI, qSOFA and their combination as a predictor of sepsis prognosis. The research method was a retrospective study design. Out of a total of 2394 MRs of patients during that period, there were only 112 MRs met the inclusion criteria and then included in this study, consisting of 42 survival and 70 un-survival outcomes respectively. Among the un-survival group, there were 41 (58,6%) have ESI 1-2, and 29 (41.4%) ESI 3-5; also 21 (30%) qSOFA more than 2, and 49 (70%) qSOFA less than 2. The sensitivity of ESI to predict the unsurvive outcome was 71.4% and its specificity was 28.6%. Meanwhile, the sensitivity of qSOFA to predict the unsurvive outcome was 30% and its specificity was 85.7%. The use of a combination of both to predict the prognosis was not significantly increased (p more than 0.05). The sensitivity of the combination of ESI and qSOFA to predict the unsurvive outcome was 61.9% and its specificity was 52.9%. So, a low ESI-score seemed to be more relevant to predicting the risk of unsurvival outcome than a high qSOFA, but a low qSOFA is more relevant to predicting the risk of survival outcome than a high ESI-score. The combination of both does not significantly increase the accuracy of the prognosis-predictor. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi kombinasi ESI, qSOFA dan kombinasinya sebagai prediktor prognosis sepsis. Metode penelitian yang digunakan adalah desain penelitian retrospektif untuk membandingkan akurasi ESI dengan qSOFA. Data yang digunakan adalah seluruh rekam medis pasien di RS Sumberglagah Mojokerto, Jawa Timur, Indonesia. Kriteria inklusi adalah rekam medis pasien berusia lebih dari 18 tahun, data lengkap meliputi tekanan darah, HR, RR, SaO2 dan kadar ESI pasien. Dari total 2394 MR pasien selama periode tersebut, hanya 112 MR yang memenuhi kriteria inklusi dan kemudian dimasukkan dalam penelitian ini, terdiri dari 42 hasil survival dan 70 unsurvival. Diantara kelompok unsurvival, ada 41 (58,6%) memiliki ESI 1-2, dan 29 (41,4%) ESI 3-5; juga 21 (30%) qSOFA 2, dan 49 (70%) qSOFA kurang dari 2. Sensitivitas ESI adalah 71,4% dan spesifisitasnya adalah 28,6% untuk memprediksi unsurvive outcome, sedangkan sensitivitas qSOFA adalah 30% dan spesifisitasnya 85,7%. Kombinasi keduanya untuk memprediksi prognosis tidak meningkat secara signifikan (p lebih dari 0,05). Sensitivitas kombinasi ESI dan qSOFA adalah 61,9% dan spesifisitasnya adalah 52,9%. Skor ESI rendah tampaknya lebih relevan untuk memprediksi risiko hasil yang tidak bertahan hidup daripada skor qSOFA tinggi, tetapi skor qSOFA rendah lebih relevan untuk memprediksi risiko hasil kelangsungan hidup daripada skor ESI tinggi. Kombinasi keduanya tidak secara signifikan meningkatkan akurasi prediktor prognosis.